Wilson disease and Menkes disease: new handles on heavy-metal transport. - Bull, P; Cox, D (1994)
Little is known at the molecular level about the homeostatic control of heavy-metal concentrations in mammals. Recently, however, two human diseases that disrupt copper transport, Menkes disease and Wilson disease, were found to be caused by mutations in two closely related genes, MNK and WND, which encode proteins belonging to the P-type ATPase family of cation transporters. The MNK and WND proteins are unique in having at their amino termini six copies of a sequence that is remarkably similar to sequences previously found in bacterial heavy-metal-resistance proteins and in a P-type ATPase that appears to form part of a bacterial copper homeostatic system. These two human ATPases are the first putative heavy-metal transporters to be discovered in eukaryotes.